Absence of Gender Effects on Attention Deficit Hyperactivity Disorder: Findings in Nonreferred Subjects - Biederman, Joseph; Kwon, Anne; Aleardi, Megan; Chouinard, Virginie-Anne; Marino, Teresa; Cole, Heather; Mick, Eric; Faraone, Stephen V. (The American journal of psychiatry, 2005)
OBJECTIVE: In a previous study, the authors found that, compared with referred boys with attention deficit hyperactivity disorder (ADHD), girls are less likely to manifest comorbid disruptive behavior disorders and learning disabilities-characteristics that could adversely affect identification of ADHD in girls. However, because referral bias can affect outcome, these findings require replication in nonreferred groups of ADHD subjects. METHOD: The authors evaluated gender effects in a large group of nonreferred siblings (N=577) of probands with ADHD and non-ADHD comparison subjects. Ninety-eight of the nonreferred siblings (N=73 males, N=25 females) met the criteria for diagnosis of ADHD, and 479 (N=244 males, N=235 females) did not meet those criteria. All siblings were systematically and comprehensively assessed with measures of emotional, school, intellectual, interpersonal, and family functioning. The assessment battery used for the siblings was the same as that used for the probands. RESULTS: The nonreferred males and females with ADHD did not differ in DSM-IV subtypes of ADHD, psychiatric comorbidity, or treatment history. They also showed similar levels of cognitive, psychosocial, school, and family functioning. CONCLUSIONS: These findings suggest that the clinical correlates of ADHD are not influenced by gender and that gender differences reported in groups of subjects seen in clinical settings may be caused by referral biases.